2000
DOI: 10.1128/cdli.7.2.218-225.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Alterations in Lipopolysaccharide-Induced Bovine Vascular Endothelial Cell Injury and Its Prevention by Sodium Arsenite

Abstract: Morphological changes, especially cytoskeletal alterations, in lipopolysaccharide (LPS)-induced vascular endothelial cell injury were studied by using LPS-susceptible bovine aortic endothelial cells (BAEC). BAEC in cultures with LPS showed cell rounding, shrinking, and intercellular gap formation. In those cells, LPS caused the disorganization of actin, tubulin, and vimentin. LPS also induced a reduction in the F-actin pool and an elevation in the G-actin pool. Cytoskeletal disorganization affected transendoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
12
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
6
12
1
Order By: Relevance
“…It is well known that arsenic induces stress proteins such as metallothionein, and heat-shock proteins HSP27, HSP32 (heme oxygenase-1), HSP 60, HSP70, and HSP90 in mammalian cells and tissues (Chakravortty et al 2000;Del Razo et al 2001a;Liu et al 2001;Parrish et al 1999;Wijeweera et al 2001). It has been reported that both sodium arsenite (10 lM) and DMA(Ñ) (5 mM) caused apoptosis in rat cerebellar neurons, and p38 and JNK3 MAP kinases and caspases played an important role in As 3+ -induced apoptosis (Namgung and Xia 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that arsenic induces stress proteins such as metallothionein, and heat-shock proteins HSP27, HSP32 (heme oxygenase-1), HSP 60, HSP70, and HSP90 in mammalian cells and tissues (Chakravortty et al 2000;Del Razo et al 2001a;Liu et al 2001;Parrish et al 1999;Wijeweera et al 2001). It has been reported that both sodium arsenite (10 lM) and DMA(Ñ) (5 mM) caused apoptosis in rat cerebellar neurons, and p38 and JNK3 MAP kinases and caspases played an important role in As 3+ -induced apoptosis (Namgung and Xia 2001).…”
Section: Introductionmentioning
confidence: 99%
“…16 In addition, increased protein tyrosine phosphorylation and activation of mitogen-activated protein kinases occur rapidly after LPS stimulation of endothelial cells. 6,17,18 The vascular endothelium is also sensitive to LPS-induced apoptosis. This effect has been demonstrated both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium arsenite (SA), a standard inducer of heat shock response, is reported to prevent LPS-induced endothelial cell injury (18 -20). Recently, we have also reported that SA inhibits LPS-induced bovine endothelial cell injury (21). Therefore, it was of particular interest to determine whether SA affected the production of harmful NO in LPS-stimulated macrophages.…”
mentioning
confidence: 99%